Factors Associated with Abnormal Imaging and Infection Recurrence after a First Febrile Urinary Tract Infection in Children - Ristola, Marko Tapani; Löyttyniemi, Eliisa; Hurme, Timo (European Journal of Pediatric Surgery, 2017)
Introduction We determined factors associated with abnormal imaging and recurrent infections after a first febrile urinary tract infection (UTI) in children younger than 3 years.Materials and Methods We retrospectively reviewed the records of all patients treated at our institute during the years 2000–2009, for a first febrile UTI in children younger than 3 years, who underwent ultrasonography and voiding cystourethrography. We evaluated data regarding factors potentially associated with abnormal ultrasonography and voiding cystourethrography results and recurrence of infections, and formulated a risk score system to assess risk of reflux and high-grade reflux.Results There were 282 patients. The only factor predicting abnormal ultrasonogram was non–Escherichia coli infection. Risk factors for vesicoureteral reflux included abnormal ultrasonogram, atypical infection, non–E. coli infection and infection recurrence. Patients with no identified risk factors for vesicoureteral reflux were unlikely to have high-grade reflux. Higher risk scores were associated with a higher risk for reflux. Non–E. coli infection was the only statistically significant predictor of infection recurrence.Conclusion All children younger than 3 years with first febrile UTI should undergo ultrasonography. Thereafter, patients with no predictive factors for vesicoureteral reflux may be followed up without further imaging. A non–E. coli infection is associated with reflux and infection recurrence.
Keywords: urinary tract infections; vesicoureteral reflux; diagnostic imaging; children